Assessing global economic activity linkages: The role played by United States, Germany and China - Emerson Fernandes Marçal; Diogo de Prince; Beatrice Zimmermann; Giovanni Merlin; Oscar Sim\~oes (EconomiA, 2020)
Economic performance increasingly relies on global economic environment due to the growing importance of trade and financial links among countries. This work aims to analyze the possible effects of a potential economic growth downturn or one large negative shock in China, Germany and United States on the growth of other economies. We use a univariate Global autoregressive approach to assess interdependence across 38 countries. We simulate two types of phenomena. The first one is a one time large shock of -2.5 standard deviations. The second experiment simulates the effect of a hypothetical downturn of the aforementioned economies. Our results suggest that the United States play the role of a global economy affecting countries all over the globe whereas Germany and China play an important regional role.
Keywords: C52; F41; F47; 330; Economic growth; International linkages; Global autoregressive